Adherence to infection prevention practices and associated factors among healthcare workers in Northeastern Ethiopia, following the Northern Ethiopia conflict - Berihun, Gete; Gizeyiatu, Adinew; Berhanu, Leykun; Sewunet, Birhanu; Ambaw, Birhanie; Walle, Zebader; Abebe, Masresha; Gasheya, Kassahun Ayele (Frontiers in Public Health, 2024)
Background In resource-limited areas, especially in conflict-affected settings, managing the risk of hospital-acquired infections is difficult due to the destruction of essential facilities in healthcare settings. The study aimed to assess adherence to Infection prevention practices and associated factors among healthcare workers in Northeastern Ethiopia following the Northern Ethiopia conflict. Methods and materials A facility-based cross-sectional study was done with 408 healthcare workers. The survey data was collected using a structured questionnaire based on published articles. Data entry and analysis was done using Epi-Data version 4.6 and SPSS version 25.0, respectively. Binary logistic regression was used to determine the association between dependent and outcome variables, with a cut-off p value 0.05 at 95% confidence interval with a p-value less than 0.05 and a 95% confidence interval for determining factors associated with adherence to infection prevention practices among study participants. Results The study included 408 healthcare workers with a response rate of 96.7%. The majority of participants were women 206 (50.5%), married 250 (61.3%), Orthodox followers 211 (51.7%), and educational status of master holder and above with a master’s degree or higher 177 (43.4%). Slightly more than half, 53.7% (219) of the respondents demonstrated safe infection prevention practices. Respondents who received training on infection prevention practices (AOR = 2.662, 95% CI: 1.361, 5.120) had an active infection prevention committee (AOR = 2.203, 95% CI: 1.359, 3.572), use infection prevention guidelines in working departments (AOR = 2.090, 95% CI: 1.013, 4.312), and access to adequate personal protective equipment (AOR = 2.773, 95% CI: 1.560, 4.929) were factors significantly associated with adherence to infection prevention practices. Conclusion Overall, only half of the respondents practiced safe infection prevention practices. Receive training on infection prevention guidelines, presence of active infection prevention committee and working guidelines, and the availability of personal protective equipment were factors of infection prevention. Hence, essential facilities like Personal protective equipment, working guidelines should be supplied by donors.